IMF Staff papers : Volume 18 No. 2. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1971)
This chapter focuses on the special drawing rights (SDR) scheme and the working of the gold exchange standard. This paper discusses the main influences involved in the relationship between SDRs and other reserve assets in a context of future reserve growth and suggests certain general conditions that may be necessary for SDRs to become the predominant source of reserve growth. The central question considered in this paper can be approached by asking in what ways the availability of SDRs as a supplement to other reserve growth should be expected to influence the basic forces operating under the gold exchange standard. The approach requiring the smallest element of international control would be to make the return on SDRs more attractive by comparison with that available on foreign exchange holdings, that is, to raise the SDR interest rate. A substantial increase in this rate would involve several separate considerations, which can be given only summary consideration here.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet